Baeyer-Villiger Rearrangement of a Substituted Pyrrole by Oxone - Kao, Joseph P. Y. (2014)
Pyrroloxyls have been reported to exhibit very narrow EPR spectral lines, essential for in vivo imaging. En route to pyrroloxyls, we observed an unexpected Baeyer-Villiger rearrangement, leading to loss of aromaticity and formation of a 4,5-dihydro-1H-ketopyrrole.